Analysis of Factors Influencing Nursing Discipline at Banda Regional General Hospital Central Maluku Regency - Mayasari, Dyah Fitrah; Harahap, Juliandi; Effendy, Ismail (Universitas Ibn Khaldun Bogor, 2025)
Background: Discipline is a crucial aspect of delivering quality healthcare services in hospitals, yet it is often overlooked. Effective service delivery can significantly enchance the overall quality of a hospital. This study aims to analyze the factors affecting the work discipline of nurses at Banda Regional General Hospital in Central Maluku. Methodology: This research employs a quantitative analytical survey design with a cross-sectional approach. The study population consists of 46 nurses employed at Banda Regional General Hospital. Data were collected using questionnaires and analyzed through Logistic Regression with significance level of α = 0,05. Results: The Chi-Square test results indicate that factors influencing the work discipline of nurses at Banda Regional Hospital include achievement, the job itself, leadership role models, close supervision and punitive sanctions. Logistic regression analysis revealed that most significant factor affecting nurses’work discipline is the job itself, with a p-value (sig) of 0,003. The limited number of nurses, coupled with the delegation of tasks that do not align with their core responsibilities, significantly increases their workload. As a results, nurses may struggle to maintain discipline in performing their duties. Conclusion: The study concludes that both internal and external factors impact the work discipline of nurses. Internal factors influencing nurse discipline at Banda Regional Hospital include achievement and the job itself. External factors include leadership role models, close supervision, punitive sanctions. Among these, the study highlights that the most influential internal factor is the job itself. Based on the findings, it is recommended that the management of Banda Regional Hospital in Central Maluku Regency implement strategies to enchance nurse discipline by addressing the influencing factors identified in this study. Additionally, nurses are expected to maintain high level of discipline and consistently deliver the highest quality of care.